2002
DOI: 10.1080/02533839.2002.9670734
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress reactions in children and adolescents one year after the 1999 Taiwan chi‐chi earthquake

Abstract: This study was to investigate the range and severity of post-traumatic stress reactions displayed by children and adolescents residing near the epicenter, one year after the Taiwan Chi-Chi Earthquake and to examine the relations of these symptoms to developmental stages and objective features of trauma exposure. Earthquake Exposure Index for Youths and Child Posttraumatic Stress Disorder Reaction Index were administered to 1,169 children and 1,201 adolescents from two heavily impacted townships. Severity of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 21 publications
2
36
0
Order By: Relevance
“…This procedure was employed by Pfefferbaum and colleagues (Pfefferbaum, Stuber, Galea & Fairbrother, 2006) in their study of PTSD after the terrorist attacks on the World Trade Center. The PTSD Reaction Index has good psychometric properties (Steinberg et al, 2004) and has been used in Taiwan in several studies (Chen et al, 2002;Chen & Wu, 2006).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This procedure was employed by Pfefferbaum and colleagues (Pfefferbaum, Stuber, Galea & Fairbrother, 2006) in their study of PTSD after the terrorist attacks on the World Trade Center. The PTSD Reaction Index has good psychometric properties (Steinberg et al, 2004) and has been used in Taiwan in several studies (Chen et al, 2002;Chen & Wu, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…The UCLA PTSD Reaction Index for DSM-IV, Revision 1, Adolescent Version (Steinberg, Brymer, Decker, & Pynoos, 2004) in traditional Chinese (Chen et al, 2002) is a self-report questionnaire. Following the diagnostic classification system for PTSD in the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV ; American Psychiatric Association, 1994), traumatic experiences and their objective features (Criterion A1) and subjective responses during or right after the trauma (Criterion A2) were first evaluated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Elementary school girls had more severe symptoms than junior high school boys. 20 Our study showed that mean scores of total difficulties score of the Strength and Difficulties was 15.07, while 40% of children fall in the abnormal Strength and Difficulties Questionnaire (SDQ)-Total Difficulties. Such results were consistent with previous studies using same instrument which showed that 42.7% of Palestinian children exposed to shelling in the Gaza Strip fall in the abnormal Strength and Difficulties Questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly different with current study carried out half of a year after the earthquake, orphans had changed their PTSD symptoms 6½ years after the 1988 Spitak earthquake. Chen et al [32] investigated PTSD symptoms in children one year and two years after Taiwan 9.21 earthquake and found that PTSD symptoms had different performances at different stages, and the overall situation was toward a positive direction over time, with a weakening trend but not much decline in avoidance and re-experience. On the other hand, from comparison results between the post-earthquake and preearthquake orphans, the latter already had significant less intrusion experience than the former, and there was no significant difference between pre-earthquake orphans and non-orphans.…”
Section: Discussionmentioning
confidence: 99%